Online Gambling Consumer Behavior: Addiction, Social Stigma, Psychological Distress, and Gender Differences - Utami, Tri; Suryani, Yulinda Erma; Marjukah, Anis; Purwaningsih, Danik Eka (Journal of Psychological Perspective, 2025)
This study investigates the differences in online gambling addiction, psychological distress, and social stigma considerations between men and women. Furthermore, this study examines the moderating role of gender in the relationship between social stigma and online gambling addiction, and between addiction and psychological distress. This research involved 191 respondents, with 128 men and 63 women. Results showed that men have significantly higher levels of addiction, psychological distress, and consideration of social stigma compared to women. Social stigma has a significant positive effect on addiction, while addiction itself has a positive impact on psychological distress for both genders. However, gender does not moderate these relationships, suggesting that the mechanisms influencing addiction and psychological distress are universal across genders. This study emphasises the need for inclusive preventive interventions, particularly targeting young men, and social support-based and empathetic educational approaches to reduce addictive behaviors and mitigate the psychological consequences of online gambling.